The Development of a Compilation of Aceh Folklore Story Containing 4c based on Flipbook Maker Application - Muhammad Yakob; Prima Nucifera; Muhammad Taufik Hidayat (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study aims to: (1) Develop a compilation of Aceh folklore containing 4C based on the Flipbook Maker application (2) Describe the feasibility of developing a compilation of Aceh folk tales containing 4C based on the Flipbook Maker application. The method in this research is research and development. Research location at SMPN Langsa City. The steps in this research are (1) Seeing Potentials and Problems with Needs Analysis (2) Data Collection (3) Product Design (4) Product Validation (5) Product Revision (6) Product Feasibility Test (7) Product Revision II. Data collection techniques in the form of observation, interviews and questionnaires. Data Analysis Techniques by describing a questionnaire containing a Likert scale and the percentage of product feasibility tests. Based on the results of the study, the following research results were obtained: 1. The results of the validation of material experts in the development of a compilation of Aceh folk tales containing 4C based on the Flipbook Maker application for students showed that the feasibility of the content was obtained with an average score of 86% with very good criteria. 2. The validation results from design experts on the feasibility of the design in the development of a compilation of Aceh folklore containing 4C based on the Flipbook Maker application scored 87% with the criteria of "very good". Thus, the feasibility of compiling Aceh folklore containing 4C based on the Flipbook Maker application developed can be used by students.